Effective Semiactive Base Isolation System under Multiple Earthquakes - Mohtasham Mohebbi; Hamed Dadkhah (Advances in Civil Engineering)
A method is proposed to design an effective semiactive control system composed of a linear low damping base isolation and a supplemental magnetorheological (MR) damper when the structure subjected to multiple earthquakes. In the proposed design method, the parameters of semiactive control system have been determined based on minimizing the average of maximum response of isolated structure under multiple design ground motions. To select appropriate value for force related weighting parameter, defined in performance index, a range has been suggested for each design objective. For numerical simulations, a scaled three-story base-isolated frame subjected to different scaled real earthquakes as well as filtered white noise excitations and the proposed method has been applied to design semiactive base isolation system under multiple earthquakes. The results of numerical simulations have shown the capability of the proposed method in designing an effective semiactive base isolation system, the performance of which under multiple earthquakes has been almost close to the case that it is designed optimally for each earthquake separately. Also, under multiple earthquakes, using the passive-off and passive-on forms of MR damper can be recommended, respectively, regarding to the objectives of minimizing the maximum acceleration and base drift.